2016
DOI: 10.1556/204.2016.38.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The integration of social media into corporate processes

Abstract: The primary aim of this paper is to give a comprehensive overview of social media marketing solutions which can be used by companies. Many authors and researchers dealing with specialised subjects examine certain areas of this topic — and, in particular, with the influence of the social media on marketing communication. An overview of current literature and practical solutions enabled us to create a framework usable in the corporate sphere for creating a social media marketing strategy and for measuring the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Critique, or what may seem like negative narratives to customer relations managers that have digital competencies, understand the opportunities within the words can be a very powerful tool for product and service innovation (Bhimani et al, 2018;Goldenberg, 2017). Additionally, the alignment of leadership in terms of governance and strategy delineation as it relates to competency and comfortability of customer relations managers is certainly a key success factor as Parsons and Lepkowski-White (2018) and Banyai (2016) asserted. Aiding managers in understanding this digital reality and navigating their space to be confident in the information and knowing the right questions to ask and approaches to enact strategy can provide the needed elements to cultivate a dynamic systems level approach as it relates to strategy enactment, marketing, and management (Courchesne, Ravanas & Pulido, 2019;Abdullah, 2016;Banyai, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Critique, or what may seem like negative narratives to customer relations managers that have digital competencies, understand the opportunities within the words can be a very powerful tool for product and service innovation (Bhimani et al, 2018;Goldenberg, 2017). Additionally, the alignment of leadership in terms of governance and strategy delineation as it relates to competency and comfortability of customer relations managers is certainly a key success factor as Parsons and Lepkowski-White (2018) and Banyai (2016) asserted. Aiding managers in understanding this digital reality and navigating their space to be confident in the information and knowing the right questions to ask and approaches to enact strategy can provide the needed elements to cultivate a dynamic systems level approach as it relates to strategy enactment, marketing, and management (Courchesne, Ravanas & Pulido, 2019;Abdullah, 2016;Banyai, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It also helps in acting as a sound substructure for identifying further social media solutions. (Banyai, 2016) The widespread use of social media as highly interactive communication channels is destined to impact how businesses approach marketing. Much prior research has found that social media is an important element in brand awareness.…”
Section: Impact Of Social Media On Business Housesmentioning
confidence: 99%
“…"Social media is defined as a group of internet-based applications that build on the ideological and technological foundations of web 2.0 and allow the creation and exchange of user-generated content" (Kaplan -Haenlein 2010: 61). Social media influenced consumer behaviour significantly, and many -previously private -consumer activities became public due to social media (Bányai 2016;Veszelszki 2018).…”
Section: Introductionmentioning
confidence: 99%